TABLES FOR THE CALCULATION OF THE PROBABILITY TO BE USED IN THE MODIFIED BONFERRONI’S TEST - Conagin, Armando (REVISTA DE AGRICULTURA, 2020)
TABLES FOR THE CALCULATION OF THE PROBABILITY TO BE USED IN THE MODIFIED BONFERRONI’S TEST